Luis I. Prádanos. Postgrowth Imaginaries: New Ecologies and Counterhegemonic Culture in Post-2008 Spain. Liverpool UP, 2018. - Shanna Lino (Studies in 20th & 21st Century Literature, 2020)
Review of Luis I. Prádanos. Postgrowth Imaginaries: New Ecologies and Counterhegemonic Culture in Post-2008 Spain. Liverpool UP, 2018. 246 pp.
Keywords: postgrowth; ecocriticism; environmental humanities; Spain